Understanding of self-management and co-management in Slovenian companies (Journal of Universal Excellence, 2026)
Research Question (RQ): Is self-management or co-management function in Slovenian companies today?Purpose: We are exploring the understanding of self-management and co-management in Slovenian companies so that we can get answers or work both forms of management and what is their connection with the autopoietic organization or company. The aim is to analyze and define the differences between self-management and co-management and their operation on the basis of ownership in Slovenian companies today. The indirect purpose is also to provide some explanations of the difference between self-management and co-management for those who do not know self-management from life, or at least from theory,The purpose of the paper is to illustrate the relationship between ownership and management methods and the connection with the autopoietic development of the company.Method: Qualitative analysis were the basis for the survey. The surveyed data were statistically processed with the LISREL program. The survey were carried out on a small sample of Slovenian economic companies of different size and activities, where there is no foreign ownership.Results: Using the triangulation method, we obtained from the qualitative analysis the acquired concepts in the survey, and with the results of the survey, the LISREL program showed the structural model of the variables. Using statistical methods, we calculated the average estimates and standard deviations of answers, which we also analyzed graphically.Organization: There are differences between self-management and co-management; the added value of the article is to raise awareness in Slovenian companies about self-management and co-management as forms of internal improvements in the operation and influence of employees on the management of companies and their contribution to the development of autopoietic organization. These would be acquisitions for the whole company.Society: The research will be a contribution to raising awareness among owners, managers, employees and the general public about social responsibility and the potential for development into a self-managing autopoietic economy.Originality: The added value of the article is in defining the differences between self-management and co-management in Slovenian companies on the basis of ownership and the connection to the development of autopoietic organization.Limitations/Future Research: The survey was conducted on a small number of Slovenian companies of different sizes. The survey covers companies without foreign ownership, not included public enterprises, no financial institutions.We propose a further survey on a larger sample of companies of different sizes; research into the development of self / co-management in autopoietic organization. We also propose a survey in the public sector. In further research we propose additional qualitative analysis with several interviews.
Keywords: self-management; co-management; ownership; autopoietic organization